Psychological Risk Factors of Functional Impairment Following COVID-19 Deaths. - Breen, Lauren; Lee, Sherman A; Neimeyer, Robert A (2021)
CONTEXT: People bereaved from COVID-19 report higher levels of grief than people bereaved from natural causes. The full impact of this onslaught of grief will not be known for some time. Ensuring high quality bereavement care in the context of COVID-19 presents unprecedented challenges to end-of-life care.